Raghib Syndrome Presenting as a Cryptogenic Stroke: Role of Cardiac MRI in Accurate Diagnosis - Vistasp J. Daruwalla; Keyur Parekh; Hassan Tahir; Jeremy D. Collins; James Carr (Case Reports in Cardiology)
Raghib Syndrome is a rare developmental complex, which consists of persistence of the left superior vena cava (PLSVC) along with coronary sinus ostial atresia and atrial septal defect. This Raghib complex anomaly has also been associated with other congenital malformations including ventricular septal defects, enlargement of the tricuspid annulus, and pulmonary stenosis. Our case demonstrates an isolated PLSVC draining into the left atrium along with coronary sinus atresia in a young patient presenting with cryptogenic stroke without the atrial septal defect. Majority of the cases reported in the literature were found to have the lesion during the postmortem evaluation or were characterized at angiography and/or echocardiography. We stress the importance of modern day imaging like the computed tomography (CT) angiography and cardiac MRI in diagnosis and surgical management of such rare lesions leading to cryptogenic strokes.